Proposed new interior design of indoor entertainment centre for Fnd mindspot at Lot 467, No.207, Jalan Bukit Bintang Seksyen 67, 55100 Wilayah Persekutuan / Nur Syarah Athirah Jamil - Jamil, Nur Syarah Athirah (Faculty of Architecture, Planning and Surveying, 2011)
Basically, the final project of interior design for final semester students is the representation of students’ understanding towards the process and important aspects of interior designing that has been studied and analyzed from the only basic knowledge of managing the project to the presentation stage of final design proposal. The project in this report is a new designed project on an indoor entertainment centre for FnD mindspot. This project is proposed to be at Lot 467, No.207, Jalan Bukit Bintang Seksyen 67, 55100 Wilayah Persekutuan. FnD mindspot is an indoor entertainment centre and the purpose of the research is to research about a new arrangement of space, using a zoning system to group together areas in terms of access and able to accomodate the customers more efficiently. The objectives are to provide a proper and permanent place for true blue gamers so they do not have to painstakingly looking for a venue to meet up and play either casually or seriously and bring them to the higher level apart from appreaciating it. The aim of this interior design project is to provide a suitable space for people to play fun activities. With all the specification and design approaches, this centre will be diverse from other entertainment centre in Malaysia. Design concept and implementation will act as profoundest study. All the data and details that has been collected from research and observation conducted, was use as a parameter in the design process.